Higher Education Hauntologies: Living with Ghosts for a Justice-to-Come - Fairchild, Nikki; Taylor, Carol (Critical Studies in Teaching and Learning, 2023)
Higher Education Hauntologies: Living with Ghosts for a Justice-to-Come (2021) (Routledge), Edited by Vivienne Bozalek, Michalinos Zembylas Siddique Motala & Dorothee Hölscher.Review by Carol A. Taylor, University of Bath, UK, https://orcid.org/0000-0002-0914-8461& Nikki Fairchild, University of Portsmouth, UK,  https://orcid.org/0000-0001-8640-2710